Structure-based design and optimization of potent inhibitors of the adenoviral protease. Issue 3 (1st February 2015) - Grosche, Philipp; Sirockin, Finton; Mac Sweeney, Aengus; Ramage, Paul; Erbel, Paul; Melkko, Samu; Bernardi, Anna; Hughes, Nicola; Ellis, David; Combrink, Keith D.; Jarousse, Nadine; Altmann, Eva
Graphical abstract